Effective use of polyvalent antivenom in snake bite dogs – A review of three cases - Pothiappan, P; Vijayakumar, H; A, Gopalakrishnan; M, Chandrasekar; S, Kavitha (Indian Journal of Veterinary Medicine, 2024)
Three dogs with snake bite presented to the critical care unit, Madras Veterinary college were taken up for this study. Affected dogs were treated with antivenom along with supportive care consisting of intravenous fluid therapy and pain management. In the present study, additional antivenin was administered in one dog with persistent clinical signs. The dose varies from 10 to 50 ml administered intravenously. It also depends on the severity of symptoms, lapse of time after the bite, size of snake and size of patient. Additional doses should be given every 2 hours as required, if symptoms such as swelling and pain persist or recur. Non-venomous snakebites are generally treated with wound cleaning, antibiotics, anti-histamines and anti-inflammatory medications.